A Recommender System for Virtual Cultural Heritage Tourism: Matrix Factorization and Collaborative Filtering Approach - Zhao, Xi; Yu, Guangyun (Informatica, 2025)
In the digital age, digital collection and recording technology can handle various types of tangible and intangible cultural heritage. Virtual tourism technology for cultural heritage has great potential in providing users with personalized experiences, but it also faces the problem of ignoring the personalized needs of different users. To this end, a user behavior classification model for cultural heritage virtual tourism technology and a cultural heritage virtual tourism recommendation model based on matrix factorization and coordinated filtering were developed. In the classification task, this study used Virtual Reality scene action data collected from HTC VIVO devices. In the recommendation task, MovieLens, Amazon-charts, ciao, and Epinions datasets were used. The findings denoted that the accuracy of the raised user behavior classification model was 85.47%, 94.62%, and 80.17% in the controller, head mounted display, and button data, respectively. In the mixed data source, the classification accuracy of the proposed model was 98.42%, and the F1 value was 97.74%. The Recall@20 of virtual tour recommendation model in MovieLens and Amazon-charts Dataset were 72.36% and 72.84%, respectively, with diversity values ranging from 0.7 to 0.9. On the Ciao dataset and Epinions dataset, the Root Mean Squared Error and Mean Absolute Error of the proposed model were 0.937 and 0.701, 1.033 and 0.796, respectively. The experimental results demonstrated that the proposed model improved classification and recommendation performance by innovatively combining additive attention mechanism, contextual multi-arm slot machine algorithm, and deep analysis of user behavior, surpassing standard matrix factorization and collaborative filtering methods. The research results help improve the display and service quality of cultural heritage virtual exhibition halls, effectively protect and inherit intangible cultural heritage, and promote the digital development of cultural resources.